2011
DOI: 10.1299/jpes.5.279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Analytical Methodology for Assessment on Seismically Induced Core Damage

Abstract: The purpose of this study is to investigate the effects of the difference between analytical methodologies for seismic probabilistic safety assessment (PSA), especially the difference in the probability of system failures and core damage sequences. We selected two methods, upper bound approximation (UBA) using minimal cut sets and direct quantification using Monte Carlo simulation (DQFM) for comparison. The former is often used in PSA for both internal and external event. The latter is developed in Japan Atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…On the other hand, it was observed that the approximation error of MCS method in point estimation can cause CDFs per accident sequence to be inconsistent in the similar degree with those presented in Ref. (8); while some accident sequences were overestimated, others were underestimated, and hence the rank of dominant accident sequences can be misleading. However, the result of this paper has shown that the inconsistency in using the MCS method abated in the uncertainty analysis since the right tails of overestimated CCDP distributions are limited by the probabilistic upper bound of 1.0.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, it was observed that the approximation error of MCS method in point estimation can cause CDFs per accident sequence to be inconsistent in the similar degree with those presented in Ref. (8); while some accident sequences were overestimated, others were underestimated, and hence the rank of dominant accident sequences can be misleading. However, the result of this paper has shown that the inconsistency in using the MCS method abated in the uncertainty analysis since the right tails of overestimated CCDP distributions are limited by the probabilistic upper bound of 1.0.…”
Section: Discussionmentioning
confidence: 55%
“…Given that objective, a hypothetical BWR plant PSA model 22 is utilized in this study because the model has been well examined and documented 8,9,12 . This model consists of five initiating events and mitigation systems to ease accident progression induced by the initiating events.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also show that it is important to choose the appropriate method among the analytical methods available even in the integrated model, and the impact on the CDF is significant as shown in the former study 13 .…”
Section: Discussionmentioning
confidence: 58%